The echoing green : memories of Victorian youth - Avery, Gillian, 1926- (New York : Viking Press, 1974)
A social history of nineteenth century England and the United States as reflected in the biographies, diaries, and letters of contemporary people
Includes bibliographical references
Keywords: Biography -- 19th century -- Juvenile literature; United Kingdom -- Social conditions -- 19th century -- Juvenile literature; United States -- Social conditions -- To 1865 -- Juvenile literature